FAKTOR-FAKTOR MENDASAR YANG MEMENGARUHI KUALITAS AUDIT: UJI EMPIRIS PADA KANTOR AKUNTAN PUBLIK WILAYAH JAKARTA - Farid Rizki Rahmatullah; Munawaroh, Munawaroh (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This studyâ€™s purpose was to analyze the effect of basic factors consisting of Competence, Independence and Audit Fees on Audit Quality at Public Accountant Firms in the Jakarta Area. Using 100 samples and regression tests symultaneously show that these basic factors have a positive and significant impact on Audit Quality. However, Â partially competence variable does not affect Audit Quality.